J1406+0102: A Dust-obscured Galaxy Hiding a Super-Eddington Accretion System with Bright Radio Emission - Hikaru Fukuchi; Kohei Ichikawa; Masayuki Akiyama; Shigeo S. Kimura; Yoshiki Toba; Kohei Inayoshi; Akatoki Noboriguchi; Toshihiro Kawaguchi; Xiaoyang Chen; Itsna K. Fitriana (The Astrophysical Journal)
Recent high- z quasar observations strongly indicate that super-Eddington accretion is a crucial phase to describe the presence of supermassive black holes (SMBHs) with M _BH  ≳ 10 ^9 M _⊙ at z  ≳ 7. Motivated by theoretical predictions that the super-Eddington phase efficiently produces outflows and bright jets in radio bands, we identify a super-Eddington radio-loud dust-obscured galaxy (DOG) J1406+0102 at z = 0.2367. This source is discovered by cross-matching the infrared-bright DOGs of A. Noboriguchi et al. with the Very Large Array/Far-Infrared and Submillimetre Telescope 1.4 GHz radio survey data and the Sloan Digital Sky Survey optical spectral catalog. J1406+0102 shows broad components in the Balmer lines, and by assuming that those lines are from the broad-line region, they give black hole (BH) mass estimations of $\mathrm{log}\,({M}_{{\rm{BH}}}/{M}_{\odot })=7.30\pm 0.25$ . Combined with an active galactic nucleus (AGN) luminosity of $\mathrm{log}({L}_{\mathrm{bol},[{\rm{O}}\,\mathrm{III}]}/\mathrm{erg}\,{{\rm{s}}}^{-1})=45.91\pm 0.38$ estimated from the intrinsic [O iii ] luminosity, this implies a super-Eddington accretion rate of λ _Edd  ≃ 3. We show that (1) J1406+0102 shows strong AGN feedback, with the [O i ii ] outflow velocity exceeding the escape velocity of the host galaxy halo and a kinetic efficiency of ≈8%, sufficient to quench the host galaxy; (2) its expected growth trajectory places it on an overmassive BH track; and (3) if representative of radio-loud DOGs, such sources can contribute significantly to the high-energy (≳100 TeV) cosmic neutrino background.